An ethnography of construction and characteristics of curriculum for inheritance of intangible cultural heritage martial arts in universities - Cheng, Yuanlong; Guo, Nana (Frontiers in Sports and Active Living, 2024)
Background Inheriting excellent traditional Chinese culture is a prerequisite for ensuring the continuity of the cultural genes of the Chinese nation. However, with the historical mission of shaping the national character of the descendants of the Chinese nation, intangible cultural heritage martial arts face the problem of an unclear curriculum content construction mechanism in university inheritance and make it difficult for these martial arts to shoulder the responsibility of cultural inheritance in the era. Method Educational ethnography as a research method is conducive to the in-depth exploration of the mechanism of curriculum content construction in the inheritance of intangible cultural heritage martial arts in universities. Results Research suggests that the construction of curriculum content for the inheritance of intangible cultural heritage martial arts in universities relies on the form of cooperation between universities and inheritors, and form three models of curriculum content construction: off campus, on campus, and on-campus cooperation. The construction of curriculum content for off-campus inheritors belongs to the “attachment style” model, which is based on the actual needs of the inheritors and the selection of boxing types. The construction of curriculum content for inheritors on campus belongs to the “reshaping” model, which is the inheritor's “simplification and reorganization” based on traditional routines and subjective and objective conditions of inheritance. The construction of course content in school local cooperation belongs to the “integrated” model, which is the reintegration of course content by universities based on their own development characteristics and the characteristics of various martial arts. Conclusion In the inheritance of intangible cultural heritage martial arts in universities, emphasis is placed on local knowledge, core skills, cultural traditions, and other characteristics, highlighting the excellence of its cultural inheritance. In the future, the focus of the inheritance of these martial arts in universities should be to cultivate innovative talents who are familiar with both traditional and modern martial arts.